Community health workers for non-communicable disease prevention and control in Nepal: a qualitative study. Issue 12 (13th December 2020) - Rawal, Lal B; Kharel, Chandani; Yadav, Uday Narayan; Kanda, Kie; Biswas, Tuhin; Vandelanotte, Corneel; Baral, Sushil; Abdullah, Abu S
Abstract : Background/objective: The increasing burden of non-communicable diseases (NCDs) in Nepal underscores the importance of strengthening primary healthcare systems to deliver efficient care. In this study, we examined the barriers and facilitators to engaging community health workers (CHWs) for NCDs prevention and control in Nepal. Design: We used multiple approaches including (a) review of relevant literature, (b) key personnel and stakeholders' consultation meetings and (c) qualitative data collection using semistructured interviews. A grounded theory approach was used for qualitative data collection and the data were analysed thematically. Setting: Data were collected from health facilities across four districts in Nepal and two stakeholder consultative meetings were conducted at central level. Participants: We conducted in-depth interviews with CHWs (Health Assistants, Auxiliary Health Workers, Auxiliary Nurse Midwife) (n=5); key informant interviews with health policymakers/managers (n=3) and focus group discussions (FGDs) with CHWs (four FGDs; total n=27). Participants in two stakeholder consultative meetings included members from the government (n=8), non-government organisations (n=7), private sector (n=3) and universities (n=6). Results: The CHWs were engaged in a wide range of public health programmes and they also deliver NCDs specific programmes such as common NCDs screening, provisional diagnosis, primary care, health education and counselling, basic medication and referral and so on. These NCD prevention and control services are concentrated in those districts, where the WHO, Package for prevention and control of NCDs) program is being implemented. Some challenges and barriers were identified, including inadequate NCD training, high workload, poor system-level support, inadequate remuneration, inadequate supply of logistics and drugs. The facilitating factors included government priority, formation of NCD-related policies, community support systems, social prestige and staff motivation. Conclusion: Engaging CHWs has been considered as key driver to delivering NCDs related services in Nepal. Effective integration of CHWs within the primary care system is essential for CHW's capacity buildings, necessary supervisory arrangements, supply of logistics and medications and setting up effective recording and reporting systems for prevention and control of NCDs in Nepal.